Japanese Clinical Practice Guidelines for Vascular Anomalies 2017. Issue 5 (22nd March 2020) - Mimura, Hidefumi; Akita, Sadanori; Fujino, Akihiro; Jinnin, Masatoshi; Ozaki, Mine; Osuga, Keigo; Nakaoka, Hiroki; Morii, Eiichi; Kuramochi, Akira; Aoki, Yoko; Arai, Yasunori; Aramaki, Noriko; et al.
Abstract: The objective was to prepare guidelines to perform the current optimum treatment by organizing effective and efficient treatments of hemangiomas and vascular malformations, confirming the safety and systematizing treatment, employing evidence‐based medicine techniques and aimed at improvement of the outcomes. Clinical questions (CQ) were decided based on the important clinical issues. For document retrieval, key words for published work searches were set for each CQ, and work published from 1980 to the end of September 2014 was searched in PubMed, Cochrane Library and Japana Centra Revuo Medicina databases. The strengths of evidence and recommendations acquired by systematic reviews were determined following the Medical Information Network Distribution System technique. A total of 33 CQ were used to compile recommendations and the subjects included efficacy of resection, sclerotherapy/embolization, drug therapy, laser therapy, radiotherapy and other conservative treatment, differences in appropriate treatment due to the location of lesions and among symptoms, appropriate timing of treatment and tests, and pathological diagnosis deciding the diagnosis. Thus, the Japanese Clinical Practice Guidelines for Vascular Anomalies 2017 have been prepared as the evidence‐based guidelines for the management of vascular anomalies.